Assesmen Kompetensi Minimum Numerasi Program Merdeka Belajar - rahmat muhdar (Jurnal Ilmiah Wahana Pendidikan, 2023)
Minimum Competency Assessment (AKM) Numerical Freedom Learning Program is one of the components that will be tested as a substitute for the National Examination (UN). The purpose of this research is to describe the teacher's perspective in implementing the Minimum Competency Assessment (AKM) in elementary schools. The perspective in question is based on the teacher's experience in the field. The research method used is descriptive qualitative research. This research was conducted on elementary school teachers in Ternate City. Data were obtained through direct interviews with elementary school teachers. From the results of the study it was concluded that teachers have a positive view of AKM because they are considered to be able to map the basic competencies needed by all students in depth and become a source of data for improving the quality of education at the elementary school level. Literacy in reading and mathematics (numeration) as measured at the AKM can be a comprehensive evaluation material for teachers and students. The implementation of AKM is not free from problems, but school elements are still trying to work together to find solutions to any problems that arise. Facilities and infrastructure are the main problems in AKM, especially schools that are unable to access technology properly